Hormonal profile in early luteal phase after triggering ovulation with gonadotropin-releasing hormone agonist in high-responder patients - Martazanova, Bella; Mishieva, Nona; Vedikhina, Irina; Kirillova, Anastasia; Korneeva, Irina; Ivanets, Tatyana; Abubakirov, Aydar; Sukhikh, Gennady T. (Frontiers in Endocrinology, 2022)
The major limitations associated with gonadotropin-releasing hormone agonist (GnRHa) triggering are inferior clinical outcomes in fresh embryo transfer cycles caused by luteal phase insufficiency following the GnRHa triggering. We included 153 high-risk patients in this study. In group I, the patients received gonadotropin-releasing hormone agonist (GnRHa) trigger + 1,500 IU human chorionic gonadotropin (hCG) support on the oocyte pick-up (OPU) day; in group II, the patients had a dual trigger (GnRHa + 1,500 IU hCG); and in group III (control), 10,000 IU hCG trigger was prescribed for the final oocyte maturation. The levels of LH, estradiol, and progesterone were evaluated in serum on the stimulation starting day, day 6 of stimulation, on the day of the trigger administration, OPU day, days 3 and 5 post-OPU, and day 14 post-ET, as well as in follicular fluid. Progesterone concentration was significantly lower in group I on OPU+5 compared to the hCG group (I vs. III, р = 0.0065). Progesterone levels were significantly lower in group II in serum on OPU+5 compared to groups I and III (I vs. II, р = 0.0068; II vs. III, р = 1.76 × 108). The progesterone levels were significantly higher in follicular fluid in group III compared to the study groups (I vs. III, р = 0.002; II vs. III, p = 0.009). However, no significant differences in clinical outcomes were found between the groups. Then, we divided all women into pregnant and non-pregnant groups and found that estradiol (p = 0.00009) and progesterone (p = 0.000036) on the day of the pregnancy test were significantly higher in the pregnant women group. Also, progesterone on OPU day was significantly higher in the non-pregnant group (p = 0.033). Two cases of moderate ovarian hyperstimulation syndrome (OHSS) late-onset occurred in group I (3.5%, 2/56), no case of moderate/severe OHSS late-onset in group II, and three cases of moderate late-onset in group III (5.7%, 3/53). The low-dose hCG supplementation improves the luteal phase insufficiency after GnRHa triggering, which is confirmed by the comparable pregnancy rates in fresh transfer cycles between the groups. However, low-dose hCG carries a similar risk of OHSS as the full dose of hCG in high-responder patients.